Taxonomic revision of the Neotropical genus Scutops Coquillett, 1904 (Diptera: Periscelididae) - Freitas, Geovânia; Ale-Rocha, Rosaly (Zootaxa, 2023)
The Neotropical genus Scutops is revised, including the description of S. flavithorax sp. nov., S. ipixunensis sp. nov., S. melinus sp. nov., S. robustus sp. nov., S. spinophallus sp. nov., and the redescriptions of five species. A key to included species is provided and Scutops striatus Hennig, 1969 is transferred to Periscelis Loew.